2016
DOI: 10.1111/jpy.12421
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative pathways in response to polyunsaturated aldehydes in the marine diatom Skeletonema marinoi (Bacillariophyceae)

Abstract: Polyunsaturated aldehydes (PUA) have recently been shown to induce reactive oxygen species (ROS) and possibly reactive nitrogen species (RNS, e.g., peroxynitrite) in the diatom Skeletonema marinoi (S. marinoi), which produces high amounts of PUA. We now are attempting to acquire better understanding of which reactive molecular species are involved in the oxidative response of S. marinoi to PUA. We used flow cytometry, the dye dihydrorhodamine 123 (DHR) as the main indicator of ROS (but which is also known to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 61 publications
2
11
0
Order By: Relevance
“…This would also be consistent with the observed concomitant decrease of NO and is supported by the strong effect of the ROS scavenger used in our experiments (Tempol), which is also known to attenuate peroxynitrite [66]. Accordingly, preliminary experiments [48] indicate a major involvement of superoxide anion (O 2 − ) and superoxide dismutase (SOD) activity with consequent H 2 O 2 formation (and H 2 O 2 -dependent downstream ROS generation) in PUA-exposed SM cells. The data were obtained using two SOD inhibitors, 2ME (2-methoxyestradiol) and DETC (sodium diethyldithiocarbamate trihydrate) and suggest an involvement of the H 2 O 2 -dependent oxidation of DHR123, as previously reported [67,68,69].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This would also be consistent with the observed concomitant decrease of NO and is supported by the strong effect of the ROS scavenger used in our experiments (Tempol), which is also known to attenuate peroxynitrite [66]. Accordingly, preliminary experiments [48] indicate a major involvement of superoxide anion (O 2 − ) and superoxide dismutase (SOD) activity with consequent H 2 O 2 formation (and H 2 O 2 -dependent downstream ROS generation) in PUA-exposed SM cells. The data were obtained using two SOD inhibitors, 2ME (2-methoxyestradiol) and DETC (sodium diethyldithiocarbamate trihydrate) and suggest an involvement of the H 2 O 2 -dependent oxidation of DHR123, as previously reported [67,68,69].…”
Section: Discussionsupporting
confidence: 90%
“…In Skeletonema costatum (now replaced as S. tropicum [47]), Chung et al [23] observed NO production in response to light stress, and this was also confirmed in SM [48]. This suggests that NO production in SM is stress-type dependent.…”
Section: Discussionmentioning
confidence: 99%
“…and thromboxanes. This phenomenon is not specific to all diatoms, since other species, such as S. marinoi, have oxylipin biosynthetic pathways producing prostanoids (Gerecht et al, 2011;Gallina et al, 2016;Di Dato et al, 2017). A first line of investigation focused on the possible production of polyunsaturated aldehydes (PUAs).…”
Section: Resultsmentioning
confidence: 99%
“…B3LF83 and Q9FPM6;Feussner and Wasternack, 2002). Therefore, P. tricornutum lacks the enzymatic equipment to produce cyclopentane-oxylipin and differs from other diatom species, such as S. marinoi, in which cyclopentane-oxylipin enzymatic pathways have been described (Gerecht et al, 2011;Gallina et al, 2016;Di Dato et al, 2017).…”
Section: P Tricornutum Lacks Genes Coding For Enzymes Synthesizing Cmentioning
confidence: 99%
See 1 more Smart Citation